Synthesis of tetrazole hybridized with thiazole, thiophene or thiadiazole derivatives, molecular modelling and antimicrobial activity - Matokah M. Abualnaja; Adel I. Alalawy; Omar M. Alatawi; Ali H. Alessa; Ahmad Fawzi Qarah; Alaa M. Alqahtani; Majid A. Bamaga; Nashwa M. El-Metwaly (Elsevier, 2024)
Background: Tetrazole-based derivatives and their electronic structures have displayed interesting antimicrobial activity. Methods: The tetrazole-based hybrids linked with thiazole, thiophene and thiadiazole ring systems have been synthesized through various chemical reactions. The computational method DFT/B3LYP has been utilized to calculate their electronic properties. The antimicrobial effectiveness was investigated against representative bacterial and fungal strains. Additionally, the synthesized derivatives binding interaction was stimulated by docking program against PDB ID: 4URO as a model of the ATP binding domain of S. aureus DNA Gyrase subunit B. Results: The structures of the synthesized tetrazole-based derivatives were confirmed by IR, NMR, and Mass spectroscopic data. The DFT/B3LYP method showed that the thiadiazole derivatives 9a-c had lower ΔEH-L than the thiophenes 7a-c and thiazoles 5a-c. The hybrids 5b, 5c, and 7b exhibited proper antibacterial activity against Gram's +ve bacterial strains (S. aureus and S. pneumonia), while 9a displayed potent activity towards Gram's -ve bacterial strains (S. typhimurium and E. coli). Meanwhile, derivatives 5a-b, 7a, 7c, and 9c showed good effectiveness towards fungal strain (C. albicans). Conclusion: The study provides valuable tetrazole core-linked heterocyclic rings and opens the door to further research on their electrical characteristics and applications. Tetrazoles and thiazoles have antibacterial properties in pharmacological frameworks, making these hybrids potential lead molecules for drug development. The conclusion summarizes the data and suggests that the synthesized chemicals' interaction with a particular protein domain suggests focused biological activity.